FCHgo: Fuel Cells Hydrogen educational model for schools, an imaginative approach to hydrogen and fuel cell technology for young students and their teachers. Issue 1 (May 2021) - Dumont, E; Fuchs, H U; Corni, F; Contini, A; Altiero, T; Romagnoli, M; Karwasz, G P
Abstract: In this paper we will describe didactic elements in the Horizon 2020 project FCHgo. This project is directed at children and adolescents between 8 and 18 years old. Its ultimate goal is to raise awareness for renewable energy sources, in particular hydrogen as a fuel and fuel cells for electric power. As part of the project, we are developing a toolkit for teachers and pupils, based upon a narrative approach to physical science and engineering. We believe the narrative approach to be best suited for this project because it allows us to take into account the cognitive tools available to pupils at various stages of their development.